Mitochondrial dysfunctions in T cells: focus on inflammatory bowel disease - Lee, Hoyul; Jeon, Jae-Han; Kim, Eun Soo (Frontiers in Immunology, 2023)
Mitochondria has emerged as a critical ruler of metabolic reprogramming in immune responses and inflammation. In the context of colitogenic T cells and IBD, there has been increasing research interest in the metabolic pathways of glycolysis, pyruvate oxidation, and glutaminolysis. These pathways have been shown to play a crucial role in the metabolic reprogramming of colitogenic T cells, leading to increased inflammatory cytokine production and tissue damage. In addition to metabolic reprogramming, mitochondrial dysfunction has also been implicated in the pathogenesis of IBD. Studies have shown that colitogenic T cells exhibit impaired mitochondrial respiration, elevated levels of mROS, alterations in calcium homeostasis, impaired mitochondrial biogenesis, and aberrant mitochondria-associated membrane formation. Here, we discuss our current knowledge of the metabolic reprogramming and mitochondrial dysfunctions in colitogenic T cells, as well as the potential therapeutic applications for treating IBD with evidence from animal experiments.